Investigating the effect of values education programmes on prosocial attitudes - Ng, Wilson Whye Shoen. (2008)
The study hopes to verify the main hypothesis, that pupils who attain high Values Education Programmes Questionaire Scores (that is pupils who consider Values Education Programmes as effective and beneficial) should also exhibit high prosocial attitudes scores measured with the Prosocial Orientation Questionaire.